Consumer Behavior in E-commerce: Evidence from Asia and Europe - Meisyaroh Catur Wulandari; Triana Septiani; Dimas Luhung Prakoso (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The COVID-19 pandemic has changed the conventional trading and direct buying. The concept of consumer shopping during a pandemic is changing the way of buying. Purchase online through third party platforms. This study identified through the SLR (Systematic Literature Review) method using the VosViewer application. The literature collected through the official website scopus.com and selected according to topics relevant to the research objectives, namely consumer behavior in Asia and Europe using e-commerce platforms during the covid-19 pandemic. The results show, research since the beginning of the COVID-19 pandemic has increased. This can be seen from the total articles in 2020 as many as 1 and 2022 as many as 16. The keywords that are the main trends are e-commerce and the covid-19 pandemic. The most popular clusters of 11 items. The results of the article review show that consumers in Asia and Europe have shifted their way of shopping, namely the type of shopping goods that are more urgent for daily needs.